Интегрально-оптические волноводные дисперсионные элементы для ВОЛС - Berikashvilli, V. S.; Klyuchnik, N. T.; Kostenko, K. N.; Yakovlev, M. Ya. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
An analysis of the current state and development trends of modern fiber-optic information transmission systems is presented. The possibility of significantly increasing the capacity of communication lines through the use of passive waveguide integrated optical structures is demonstrated. Schemes of promising planar dispersion elements are provided. The features of the technology for producing dispersion elements based on comb channel waveguides with increased content of doping additives, which enhance both material and waveguide dispersion, are discussed.